Escaping the crowd: An experimental study on the impact of a Virtual Reality experience in a shopping mall - Van Kerrebroeck, Helena; Brengman, Malaika; Willems, Kim (Computers in human behavior, 2017)
Crowding is largely associated with negative consumer outcomes such as shopping irritation and lower levels of shopping pleasure, less positive attitudes and less satisfaction toward the crowded store or mall. While previous research demonstrated the alleviating effect of slow music and greenery on this negative impact of high perceived crowding, this study examines the potential of a relaxing Virtual Reality (VR) experience in a shopping mall. As Virtual Reality immerses users in a computer-generated environment, and as such allows them to escape the hectic mall environment, its use is expected to result in a more positive consumer experience. In a quasi-experimental 2 × 2 between-subjects design, the levels of attitude toward the mall, approach behaviour, mall satisfaction, and loyalty intentions were measured as well as perceived crowding. Participants in the experimental condition were exposed to a relaxing Virtual Reality experience in the mall, whereas participants in the control condition did not get such a treatment. Overall, consumers reported more positive responses on all measured outcome variables after being exposed to the Virtual Reality experience. In addition, the effect on mall attitudes, satisfaction and loyalty is more pronounced when crowding is perceived to be high. •VR experience can be an effective tool to alleviate perceived mall crowding.•VR experience positively affects consumer attitudes and responses toward the mall.•The beneficial effects of VR are most pronounced in case of high perceived crowding.